Incentives and quota prices in an emission trading scheme with updating - Knut Einar Rosendahl (Statistics Norway, Research Department, 2007)
Emission trading schemes where allocations are based on updated baseline emissions give firms less incentives to reduce emissions. Nevertheless, according to Böhringer and Lange (2005a), such allocation schemes are cost-effective if the system is closed and allocation rules are equal across firms. In this paper we show that the cost-effective solution may be infeasible if the marginal abatement costs grow too fast. Moreover, if a price cap or banking/borrowing are introduced, the abatement profile is no longer the same as in the case with lump sum allocation. In addition, we show that with allocation based on updated emissions, the quota price will always exceed the marginal abatement costs. Numerical simulations indicate that the quota price most likely will be several times higher than the marginal abatement costs, unless a significant share of allowances are either auctioned or lump sum distributed.
Keywords: H21; Q28; 330; Emission trading; Allocation of quotas; Quota prices.